Dreams of the US President 2024. - Bulkeley, Kelly; Lane, Jennifer Marie (ReVision)
This article examines the collective dimension of dreaming in relation to the 2024 U.S. Presidential election, presenting findings from a survey of 3,055 American adults conducted by YouGov on behalf of the Sleep and Dream Database. It explores how dreams about political figures, particularly Donald Trump and Kamala Harris, reflect social and emotional responses to the election, with Trump appearing more frequently in dreams than Harris. The study applies sociologist Max Weber’s concept of charisma to interpret the frequency and relational quality of politicians’ appearances in dreams as indicators of their charismatic authority. The results suggest that politically themed dreaming occurs broadly across ideological lines and may offer insights into the social psychology of political leadership and collective concerns.